A question of justice: are holiday clubs serving the most deprived communities in England?. Issue 10 (3rd October 2018) - Mann, Emily; Long, Michael A.; Stretesky, Paul B.; Defeyter, Margaret Anne
ABSTRACT: In response to the problem of holiday hunger, hundreds of local "holiday clubs" have recently been established across the UK. This research examines the spatial relationship between income, childhood deprivation, ethnicity and holiday clubs across 32, 844 Lower Super Output Areas (LSOAs) in England to determine if these clubs are currently operating in an inclusive fashion. Data on the location of holiday clubs comes from a national survey. Binary logistic regression results suggest that holiday clubs are likely to operate in economically disadvantaged areas. At the same time, clubs are not distributed equally by ethnicity. That is, holiday clubs operated by voluntary organisations are more likely to be situated in LSOAs that are disproportionately white and English\British and less likely to be situated in LSOAs that are disproportionately ethnic minority. This finding has important implications for the pursuit of holiday clubs as a policy mechanism for addressing access to food in light of the state's failure to adequately feed all of the country's children.